Pemberdayaan masyarakat untuk umkm melalui pelatihan penyusunan proposal usaha dan analisis laporan keuangan UMKM di Kabupaten Kampar - Julita Julita (Unri Conference Series: Community Engagement, 2020)
The aim of this activity is to Micro-Small and Medium Enterprises (MSMEs) be able to compile Business Proposals and be able to analyze financial statements, so that the realization of MSMEs becomes an efficient, healthy and high-growth business, and able to become the people's economic strength and make a large contribution to national economic development. The method of this service activity is the direct survey method for MSMEs without gathering participants, this method was chosen by considering mutual security because it is still in Covid-19 pandemic. The stages of this service activity begin by explaining the obstacles that are often faced by MSMEs, then explaining the importance of business proposals, tips and tricks for preparing business proposals, and the importance of financial statements analyzing. Results achieved: has provided skills and knowledge to MSMEs, especially in Kampar regarding Business Proposals and Financial Statement Analysis even though in limited due to the Covid-19 pandemic.